THE IMPACT OF FINANCIAL LITERACY AND HEDONISM LIFESTYLE TOWARD FINANCIAL MANAGEMENT (STUDY OF STUDENTS OF UNIVERSITAS DIPONEGORO) - Satwyan Prabu Dhira Dharmika; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2026)
Abstract: A person's level of well-being can be seen from how well a person manage the finances. Financial literacy is believed to help people to manage finances well and achieve financial goals in the future. The better a person's understanding of financial literacy, the wiser a person in managing finances. On the other hand, a hedonism lifestyle encourages someone to behave consumptively which can worsen the quality of a person's financial management. Students are in a transition period towards adulthood. The skills that students must have before entering adulthood and the world of work are skills in managing finances well, but sometimes students are still unable to manage finances well and some of the students have a lifestyle that tends to be hedonistic. This research aims to analyse the influence of financial literacy and hedonism lifestyle on financial management behavior in Universitas Diponegoro students. Using a quantitative approach, this research involved 330 active students selected using purposive sampling techniques. Data collection was conducted through questionnaires and analysed using SmartPLS software. The results showed that financial literacy has a positive and significant influence on students' financial management behavior. In addition, a hedonism lifestyle was found to have a significant influence, although smaller than financial literacy, on students' financial management. These findings suggest that increasing financial literacy can help students manage their finances better, while a hedonistic lifestyle tends to contribute to less than optimal financial management behavior.